2020
DOI: 10.1590/1980-5373-mr-2019-0605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Microstructure on the Wear Resistance of a Pearlitic Steel

Abstract: Despite the experimentation of bainitic and martensitic microstructures in wheel-rail steels, pearlitic microstructure remains dominant in railway track. The wear resistance behavior of bainitic and pearlitic microstructures is still a matter of controversy. In this study, pin-on-disc sliding wear tests were performed to analyze the effects of the microstructure on wear resistance. The AISI 1080 steel was isothermally treated at five temperatures using a dilatometer in order to obtain pearlite, bainite and mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
4
0
4
Order By: Relevance
“…Control‐cooled rails have smaller interlamellar spacing, therefore higher hardness, around 340–390 HB. [ 7,8 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Control‐cooled rails have smaller interlamellar spacing, therefore higher hardness, around 340–390 HB. [ 7,8 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a limit to the hardness that can be achieved with conventional pearlitic rail steels, without impairing the material toughness. [ 7,8 ] Therefore, the production of alternative microstructures such as bainitic has been considered; it can result in higher hardness than what is achieved by conventional pearlitic steels and not incur significant toughness loss. According to recent studies, bainitic steels for railway applications can reach tensile strength up to 1400 MPa and total strain between 15% and 18%.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that by maximizing the hardness of the pearlitic structure, the wear rate is minimised in both laboratory and field tests. 9,10 It was also found that the wear resistance increases with decreasing inter-lamellar spacing. 10 Available data in the literature indicate that in the past 50 years the railways and rail manufacturers have improved rail performance by increasing hardness from 248 HB to more than 400 HB.…”
Section: Introductionmentioning
confidence: 97%
“…9,10 It was also found that the wear resistance increases with decreasing inter-lamellar spacing. 10 Available data in the literature indicate that in the past 50 years the railways and rail manufacturers have improved rail performance by increasing hardness from 248 HB to more than 400 HB. The historical path followed in the development of premium grade (high-performance) steel metallurgy is illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 97%
“…Zener (1945) Em geral, aços com estrutura perlítica lamelar fina apresentam uma boa relação entre propriedades mecânicas, resistência ao desgaste e propriedades térmicas (BHADESHIA;HONEYCOMBE, 2006). Foi observado que quanto menor o espaçamento interlamelar da perlita, maior é a dureza e a resistência ao desgaste do material quando submetido a ensaios tribológicos de deslizamento puro (CHAVES et al, 2020).…”
Section: Microestrutura Perlíticaunclassified